The Predictive Power of Voting Power Indices: FASB Voting on Statements of Financial Accounting Standards Nos. 45-69 - Selto, Frank H.; Grove, Hugh D. (Journal of Accounting Research, 1983)
Frank H. Selto, Hugh D. Grove, The Predictive Power of Voting Power Indices: FASB Voting on Statements of Financial Accounting Standards Nos. 45-69, Journal of Accounting Research, Vol. 21, No. 2 (Autumn, 1983), pp. 619-622